Dasatinib enhances tumor growth in gemcitabine-resistant orthotopic bladder cancer xenografts. (December 2016) - Vallo, Stefan; Michaelis, Martin; Gust, Kilian; Black, Peter; Rothweiler, Florian; Kvasnicka, Hans-Michael; Blaheta, Roman; Brandt, Maximilian; Wezel, Felix; Haferkamp, Axel; Cinatl, Jindrich
Abstract Background Systemic chemotherapy with gemcitabine and cisplatin is standard of care for patients with metastatic urothelial bladder cancer. However, resistance formation is common after initial response. The protein Src is known as a proto-oncogene, which is overexpressed in various human cancers. Since there are controversial reports about the role of Src in bladder cancer, we evaluated the efficacy of the Src kinase inhibitor dasatinib in the urothelial bladder cancer cell line RT112 and its gemcitabine-resistant sub-line RT112r GEMCI20 in vitro and in vivo. Methods RT112 urothelial cancer cells were adapted to growth in the presence of 20 ng/ml gemcitabine (RT112r GEMCI20 ) by continuous cultivation at increasing drug concentrations. Cell viability was determined by MTT assay, cell growth kinetics were determined by cell count, protein levels were measured by western blot, and cell migration was evaluated by scratch assays. In vivo tumor growth was tested in a murine orthotopic xenograft model using bioluminescent imaging. Results Dasatinib exerted similar effects on Src signaling in RT112 and RT112r GEMCI20 cells but RT112r GEMCI20 cells were less sensitive to dasatinib-induced anti-cancer effects (half maximal inhibitory concentration (IC50 ) of dasatinib in RT112 cells: 349.2 ± 67.2 nM; IC50 of dasatinib in RT112r GEMCI20 cells: 1081.1 ± 239.2 nM). Dasatinib inhibited migration of chemo-naive and gemcitabine-resistant cells. Most strikingly, dasatinib treatment reduced RT112 tumor growth and muscle invasion in orthotopic xenografts, while it was associated with increased size and muscle-invasive growth in RT112r GEMCI20 tumors. Conclusion Dasatinib should be considered with care for the treatment of urothelial cancer, in particular for therapy-refractory cases.